Metode Microsoft Clustering untuk Meningkatkan Potensi Penerimaan Mahasiswa Baru - Suharyadi, Suharyadi; Sediyono, Eko (Jurnal Sistem Komputer, 2017)
The competition among private universities in Indonesia for students admission is getting tough. This phenomenon is triggered by the fact that the main source of income for those universities is from their students. In order to win the competition is the targeting the promotion to the right area. Clustering method in data mining could be utilized get the information on the segment of prospective students, By segmenting these prospective students, a good promotion could be carried out in a more organized way. It also helps to achieve the cost effective and the target that the universities have. One of the advantages of this kind of promotion is minimizing the promotion costs and the increasing responses from prospective students. This model is built using the ready to use tool in the market,Microsoft Excel and SQL Server 2008 Data Mining Add in. By implementing thus segmenting process to the applicant, it could classify which areas contributing to the number of the prospective students and which major they are interested in.